Current Advances in Amyotrophic Lateral Sclerosis - Estévez, Alvaro G. (IntechOpen, 2013)
Our understanding of the pathology of amyotrophic lateral sclerosis is a continuously changing field. New hypotheses are generated with each new discovery; they are abandoned to be reanalyzed after some time under the light of new observations. This book present a series of reviews from experts in different aspects of the disease focus on these hypotheses. There are also a few review chapters providing clear examples of these new observations that make the field to reanalyze previous conclusions.